2022
DOI: 10.3389/fchem.2021.827085
|View full text |Cite
|
Sign up to set email alerts
|

Energy Redistribution Following CO2 Formation on Cold Amorphous Solid Water

Abstract: The formation of molecules in and on amorphous solid water (ASW) as it occurs in interstellar space releases appreciable amounts of energy that need to be dissipated to the environment. Here, energy transfer between CO2 formed within and on the surface of amorphous solid water (ASW) and the surrounding water is studied. Following CO(1Σ+) + O(1D) recombination the average translational and internal energy of the water molecules increases on the ∼10 ps time scale by 15–25% depending on whether the reaction takes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…For the process in gas phase all necessary interactions are accounted for in one global energy function 190 whereas for the process on amorphous solid water the reorganization of the electrons between the CO + O reactant and the CO 2 product needs to be included explicitly. 45,269…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the process in gas phase all necessary interactions are accounted for in one global energy function 190 whereas for the process on amorphous solid water the reorganization of the electrons between the CO + O reactant and the CO 2 product needs to be included explicitly. 45,269…”
Section: Discussionmentioning
confidence: 99%
“…For the process in gas phase all necessary interactions are accounted for in one global energy function 190 whereas for the process on amorphous solid water the reorganization of the electrons between the CO + O reactant and the CO 2 product needs to be included explicitly. 45,269 Conformationally dependent electrostatics has already been explored to some extent in the past. 270 However, the applications were often restricted to water 93 with the exception of the fluctuating charge implementation in CHARMM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermoneutral atom-exchange reaction (CO A + O B → CO B + O A ) has already been considered in the context of stabilizing CO 2 on amorphous solid water (ASW) to better understand molecule formation at astrophysical conditions. 70,71 For this process it was found that for bulk temperatures of ∼ 50 K formation and stabilization of CO 2 is very likely (60 % of the trajectories stabilize). Together with the present results this suggests that quantum effects will only marginally affect this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…For the process in gas phase all necessary interactions are accounted for in one global energy function 163 whereas for the process on amorphous solid water the reorganization of the electrons between the CO+O reactant and the CO 2 product needs to be included explicitly. 37,243 Conformationally dependent electrostatics has already been explored to some extent in the past. However, the applications were often restricted to water 85 with the exception of the fluctuating charge implementation in CHARMM.…”
Section: Discussionmentioning
confidence: 99%